Treatment of dilated cardiomyopathy with dynamic cardiomyoplasty: the Heidelberg experience - Lange, Rüdiger; Sack, Falk-Udo; Voss, Bernhard; De Simone, Raffaele; Thielmann, Matthias Klaus; Nair, Angélique; Brachmann, Johannes; Haußmann, Rainer; Fleischer, Franz; Hagl, Siegfried (The annals of thoracic surgery, 1995)
Background. - Data concerning the efficacy of dynamic cardiomyoplasty are still inconsistent, especially in terms of improvement of left ventricular function. - Methods. - Between August 1990 and February 1994, eight isolated cardiomyoplasty procedures were performed in patients with cardiomyopathy (ejection fraction, 0.14 to 0.32; New York Heart Association class III) and contraindications to heart transplantation. - Results. - Follow-up was 41.1 ± 14.1 months. One patient died 2 months and another 3 years after operation. Considerable symptomatic improvement was found in 6 of 7 patients, 3 of whom went back to work. One patient with severe pulmonary hypertension exhibited no improvement. Mean New York Heart Association-class decreased from 3.0 to 1.9 (p < 0.001). Echocardiography showed an increase in fractional shortening and in peak aortic flow velocity in all patients. Left ventricular ejection fraction increased from 0.21 ± 0.05 to 0.38 ± 0.16 (n = 7, p < 0.015) at 1 year, to 0.37 ± 0.18 (n = 6, p < 0.05) at 2 years, and to 0.36 ± 0.19 (n = 5, not significant) at 3 years. Pulmonary artery pressure tended to decrease over time. No significant change in exercise level or maximal oxygen consumption during treadmill testing was observed. - Conclusions. - Our preliminary results show that patients may exhibit an impressive clinical improvement after cardiomyoplasty, with only moderate changes in objective hemodynamic indices. We do not consider cardiomyoplasty an alternative to heart transplantation, but reserve it for patients with contraindications to heart transplantation.
Elektronische Reproduktion der Druck-Ausgabe 5. April 2000
Gesehen am 15.05.2024